Development of predicting equations for slip modulus and shear capacity of CLT–concrete composite with screw connections. (15th July 2023) - Jeong, Gi Young; Pham, Van Sy; Tran, Dang Khai
Abstract: This study investigated the effects of density, screw inclination angle, and screw arrangement on the slip modulus and shear capacity of a screw connection for a cross-laminated timber (CLT) concrete composite (CCC). A total of 35 push-out tests were conducted to investigate slip modulus and shear resistance of the CCC using a self-tapping screw. The test results identified double and single plastic hinges in the screw as the main failure mechanisms in the CLT–concrete screw connection. Compared to pine CLT, the CCC screwed connections with larch CLT showed a greater slip modulus of 18.5–55.1%, higher shear resistance of 44.1–79.2%, but a ductility ratio 17.6–25.4% lower. The CCC screwed connections with a screw angle of 60° showed the lowest slip modulus and shear resistance compared to those with screw angles of 90° and 45°. When two screws with an angle of 45° and 135° in the X-layout were installed, the shear properties of the CCC screwed connections with larch and pine CLT differed by only up to 11%. A newly developed model for the shear modulus and shear resistance of the CCC using a self-tapping screw differed by 17.48% for the slip-modulus and 29.52% for the shear capacity between the predicted and experimental values. Highlights: Different effects of CLT density on slip modulus and shear capacity of CCC evaluated. Effects of screw angle and arrangement on shear properties of CCC analyzed. Main failure mechanism of CCC under shear compression and tension load evaluated. Predicting equations for CCC slip modulus and shear capacity with screw developed.